The Kingdom صورة الأنا في الملصق الإشهاري لفيلم الأمريكي - عبد الناصر, مليك; زينب, قوني (جامعة الوادي - University of Eloued, 2022)
ملخص: تحاول هذه الورقة البحثية التعرف على صورة الأنا العربي في المخيال الأمريكي من خلال دراسة الملصق الإشهاري لفيلم أمريكي (بعنوان المملكة The Kingdom)، حيث تعتبر اللافتة الإعلانية رسالة بصرية تحتوي على طاقة تأثيرية كبيرة تسيطر على تشكّل وعي المتلقي لما تحويه من قدرات إغرائية تعتقل عقله وتسيطر على سلوكه؛ فاللافتة الإشهارية للفيلم هي العتبة الأولى للنص الفيلمي التي يقف عليها المتلقي وتشدّه إلى العمل الفني لما تكتنزه من شفرات لغوية تتقاطع فيها عدة فنون تهدف إلى جذب المتلقي والتأثير والسيطرة عليه. يبتدئ البحث بمدخل نظري يتناول مفاهيم الصورة،الأنا،الملصق الإشهاري للفيلم، ويتطرق لعرض لمحة تاريخية لصورة العربي في المخيال الغربي، ثم دراسة تحليلية توظف أدوات المنهج البنيوي والمنهج السيميائي للوقوف على الدلالات الإيحائية للملصق الإشهاري التي تسهم في تشكيل صورة العربي في المخيال الأمريكي. Abstract This research paper aims to identify the Arabian ego image in the American imagination through studying the advertising poster of an American movie (entitled The Kingdom), where the advertising banner is considered as a visual message that contains influential energy for the recipient that controls the formation of his consciousness due to the seductive capabilities it contains that arrest his mind and control his behavior. The advertising sign of the film is the first threshold in the film text; on which the recipient stands and it makes him accept the artwork because it contains linguistic codes that intersect several arts that work for attracting, influencing and controlling the recipient. The research begins with a theoretical introduction that deals with the concepts of the image, the ego, and the advertising poster of the film, and deals with presenting a historical overview of the Arab image in the Western imagination, then an analytical study that employs the tools of the structural approach and the semiotic method to find out the suggestive connotations of the advertising poster that contribute to the formation of the Arab image in the American imagination.
مقال
Keywords: الصورة ; الأنا ; الملصق ; الإشهاري ; الفيلم ; الأمريكي